Survey on conditioning-related main factors and the practices of Japanese National Sports Federations for Tokyo 2020 and Beijing 2022 Olympic and Paralympic Games - Hanaoka, Y.; Nakamura, Y.; Shimizu, K.; Kinugasa, T.; Shirai, K.; Kukidome, T. (Journal of High Performance Sport, 2024)
National Sports Federations (NF) are the closest supporter of elite athletes; their initiatives can significantly impact elite athletes' performance in major competitions. In this study, we identified 10 main factors that might contribute to athletes' performance in major competitions and investigated how Japanese NF addressed these factors in the Tokyo 2020 and Beijing 2022 Olympic and Paralympic Games. This study aimed to evaluate the impact of practices that Japanese NF implemented in Tokyo 2020 and the Beijing 2022 Olympic and Paralympic Games. The national survey was conducted via an online questionnaire after a competition for the Japanese NF staff who participated in the Tokyo 2020 or Beijing 2022 Olympic and Paralympic Games. The participants were asked about their goal achievement, main factors (technical skills, fitness, physical preparation, injury management, infection control, mental health, nutrition, scheduling, equipment support, and strategy/tactics), and the impact of the COVID-19 pandemic on their performance and preparation. Forty-three NF staff members responded to the survey. Statistically significant differences were found between medal-winning and non-medal-winning NF in goal achievement. Interestingly, significant differences were also found in other factors of fitness, mental health, and strategy/tactics between medal-winning and non-medal-winning NF. A comparison of the practices conducted by each NF in preparation for the Tokyo 2020 and Beijing 2022 Olympic and Paralympic Games revealed that improving all crucial factors related to conditioning for winning medals is crucial. Thus, based on the findings of this study, we suggest that strengthening fitness, mental health, and strategy/tactics are particularly important for elite Japanese athletes preparing for major competitions.